Analisis Inovasi Platform Integrasi Belanja Pemerintah melalui Digipay: Pemberdayaan UMKM dan Bangga Produk Indonesia dalam kacamata New Public Governance: Bahasa Indonesia - Tawaris, Riet; Wardiyanto, Bintoro (Universitas Nahdlatul Ulama Blitar, 2025)
This study analyzes the implementation of the DigiPay platform for MSME Empowerment and Proud of Indonesian Products from the perspective of New Public Governance (NPG), with Diffusion of Innovations Theory as the incorporated theory. The goal of DigiPay is to increase efficiency, transparency, and inclusion in government procurement of goods and services. The results show that DigiPay successfully integrates various stakeholders, including the government, the banking sector, and small and medium enterprises (MSMEs), in a digital ecosystem. This digital ecosystem supports MSME empowerment and local product marketing, and DigiPay also accelerates the procurement administration process. However, infrastructure and technological literacy still hinder the adoption of DigiPay. This research suggests improving ease of use and involving more people in adoption by using the Diffusion of Innovations Theory. To support sustainable and inclusive digital transformation, this research suggests that future researchers should strengthen cross-sector collaboration and digital education. This will also strengthen the MSME sector as part of the national economy.